THE MORAL DEVELOPMENT OF THE MAIN CHARACTER SEBASTIAN WILDER PORTRAYED IN LA LA LAND MOVIE (2016) - Riska Fitriani; M. Natsir; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
ABSTRACT Literature and life is an artful way to sensitize on various complex issues and uses educative power that literatures have. The study is trying to consider the role of literature in moral education. The research problems of this study is what are the moral development of the main character, Sebastian Wilder portrayed in La La Land movie? The researcher includes six stages of Lawrence Kohlberg’s Moral development theory which have three levels; pre-convention level, convention level and post-convention level. Each levels have two stages; stage one obedience and punishment orientation and stage two individualism and exchange for pre-convention level, stage three good interpersonal relationship and stage four maintaining the social order for convention level, and stage five social control and individual rights and stage six universal principles for post-convention level. Six stages of moral development theory can help the researcher analyzed how moral development on Sebastian Wilder is in La La Land movie by Damien Chazelle. In this study the researcher find six stages of Lawrence Kohlberg’s moral development that portrayed the main character, Sebastian Wilder. The first stage, is when Sebastian thinks the advice from the big people that he should do is only just an advice. The second stage is he loves himself as he being alone and loving what he is doing on his own. In the third stage, he tries to make a real effort to get a good behavior to keep his relationship with his friends or his family always good. The fourth stage is he thinks that he must to organize the things from the social order to keep his life better. The fifth is when he gets a steady job and he must do everything with his new band. The sixth, he changed his future because he think that he must to be a successful person and get the popularity the same with the other musicians. Keywords: moral development, main character, La La Land movie ABSTRAK Sastra dan kehidupan adalah sebuah seni untuk membuat kepekaan di berbagai macam permasalahan yang kompleks dan menggunakan kekuatan pendidikan yang terdapat dalam sastra. Penelitian ini mencoba untuk mempertimbangkan peran sastra dalam pendidikan moral. Permasalahan penelitian ini adalah; apa saja perkembangan moral yang ada pada pemeran utama, gambaran Sebastian Wilder pada film La La Land? Peneliti memasukkan enam tingkat pada Teori Perkembangan Moral oleh Lawrence Kohlberg, yang mana memiliki tiga level; pre-convention level, convention level dan post-convention level. Di setiap level memiliki dua tingkatan, yang mana teori tingkatan-tingkatan tersebut membantu peneliti menganalisa bagaimana perkembangan moral pada Sebastian Wilder di film La La Land oleh Damien Chazelle di analisis. Pada penelitian ini peneliti mendapatkan enam tingkatan Teori Perkembangan Moral oleh Lawrence Kohlberge pada gambaran pemeran utama, Sebastian Wilder. Tingkatan pertama, saat Sebastian berpikir bahwa nasihat dari orang-orang penting yang seharusnya dia lakukan itu hanyalah sebuah nasihat yang tidak harus dilakukan. Tingkatan kedua adalah bagaimana dia merasa nyaman akan kesendiriannya dan menyukai apa yang dia lakukan untuk dirinya sendiri. Pada tingkatan ketiga, dia mencoba untuk membuat sebuah usaha yang nyata untuk mendapatkan perilaku yang benar dan baik agar dapat menjaga hubungan antar teman dan keluarga. Tingkatan keempat, dia memikirkan untuk lebih mengatur kehidupan sosialnya menjadi lebih baik. Tingkatan kelima saat dia mendapatkan kerja tetap dan melakukan semua hal untuk band baru yang sedang dijalaninya. Tingkatan keenam, dia mengubah masa depannya karena dia berpikir bahwa dia seharusnya menjadi orang yang sukses dan mendapatkan popularitas yang setara dengan musisi pada umumnya. Kata Kunci: perkembangan moral, tokoh utama, film La La Land